A Review of Macrophage Migration Inhibitory Factor in Tumourigenesis - Hartnett, Jack (Trinity Student Medical Journal, 2016)
With its unique tautomerase activity, macrophage migration inhibitory factor (MIF) is a multi-functional pro-inflammatory cytokine implicated in the pathogenesis of numerous types of cancer. Through a variety of mechanisms MIF is tumourigenic, pro-inflammatory and pro-angiogenic. As a result of its central role in both cancer and inflammation many MIF inhibitors are currently in development, with recent studies yielding impressive results.